2023
DOI: 10.3724/abbs.2023010
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA <italic>ELFN1-AS1</italic> promotes proliferation, migration and invasion and suppresses apoptosis in colorectal cancer cells by enhancing <italic>G6PD</italic> activity

Abstract: Tumour cells change their metabolic patterns to support high proliferation rates and cope with oxidative stress. The lncRNA ELFN1-AS1 is highly expressed in a wide range of cancers and is essential to the proliferation and apoptosis of tumour cells. Nevertheless, its function in the metabolic reprogramming of tumour cells is unclear. Here we show that ELFN1-AS1 promotes glucose consumption as well as lactate and NADPH production. Database searching, bioinformatics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…LncRNAs are a class of transcripts exceeding 200 nucleotides in length that are characterized by minimal or no protein-coding potential [18][19][20]. LncRNAs were dismissed ″garbage products″ of transcription, but in the past two decades, their involvement in cell proliferation [21,22], apoptosis [23][24][25], metastasis [26,27], and differentiation [28] has been revealed. Furthermore, lncRNAs regulate tumorigenesis and disease progression at both the transcriptional and posttranscriptional levels [29].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs are a class of transcripts exceeding 200 nucleotides in length that are characterized by minimal or no protein-coding potential [18][19][20]. LncRNAs were dismissed ″garbage products″ of transcription, but in the past two decades, their involvement in cell proliferation [21,22], apoptosis [23][24][25], metastasis [26,27], and differentiation [28] has been revealed. Furthermore, lncRNAs regulate tumorigenesis and disease progression at both the transcriptional and posttranscriptional levels [29].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, they enhanced proliferation, invasion, and migration and decreased apoptosis in CRC cell lines. In addition, in vivo experiments revealed that the overexpression of ELFN1-AS1 is associated with a larger tumor xenograft in nude mice.In another study, Fahong Wu et al [ 33 ] demonstrated that ELFN1-AS1 activated the pentose phosphate pathway (PPP) by increasing glucose-6-phosphate dehydrogenase (G6PD) expression. Consequently, ELFN1-AS1 could enhance the malignant characteristics of CRC both in vivo and in vitro by interfering with metabolic pathways.…”
Section: Elfn1-as1 Deregulation In Cancermentioning
confidence: 99%
“…Therefore, TP53 could deprive cancer cells of glucose, the primary substrate for PPP [ 60 63 ]. Fahong Wu et al [ 33 ] found that ELFN1-AS1 promotes G6PD activity by inducing the degradation of TP53 protein in CRC. The increased G6PD leads to an accumulation of NADPH.…”
Section: Elfn1-as1 Mechanism Of Action In Cancermentioning
confidence: 99%
“…Further research has revealed the DLGAP1-AS2/CTCF/Myc axis as an oncogenic regulatory pathway in CRC, promoting CRC cell proliferation ( 213 ). Multiple studies have shown that ELFN1-AS1 is highly expressed in CRC and promotes CRC proliferation through various regulatory axes ( 95 , 214 , 215 ). Overexpression of FAM230B promotes tumor growth by increasing the levels of immature miR-1182 in CRC cells, while simultaneously inhibiting the expression levels of mature miR-1182 ( 101 ).…”
Section: Regulation Of Cell Proliferation By Lncrnasmentioning
confidence: 99%